Regularidade dos conjuntos de Julia - Silva, Paulo Ricardo da (1990)
In this work we present a sistematic exposition of a result due to R. Maiíé and L. Rocha, who proved that the Julia set of a rational map of the Riemann sphere is uniíormly perfect. We start with necessary basic concepts and dose with a proof of a result of C. Pommerenke which allows us to condude the Dirichlet regularity of the Julia set.